Learning from other Domains to Advance AI Evaluation and Testing: The regulatory landscape of nanoscience and nanotechnology, and applications to future AI regulation - Dionne, J. (2025)
The fields of nanoscience and nanotechnology investigate and manipulate matter at the nanoscale (generally defined as having critical dimensions less than 1000nm). At these scales, materials exhibit distinct physical, chemical, and biological properties compared to their bulk counterparts due to their increased surface area, enhanced reactivity, and potential for quantum effects. Nanomaterials include nanoparticles, two-dimensional materials (such as graphene, hexagonal boron nitride, transition-metal dichalcogenides), and their heterostructures, and are pivotal to the development of advanced technologies across numerous industries. These materials have the potential to revolutionize a wide range of sectors, from computing, communications, and catalysis, to medicine and manufacturing, owing to their increased strength, improved conductivity, and/or the ability to interact with biological systems in novel ways. The Nanotechnology Research and Development Act recently celebrated its twentieth anniversary (March 2004-March 2024). As stated in former President Bill Clinton’s letter during that celebration, “in the last quarter century, nanotechnology research has contributed to scientific breakthroughs that have changed the way we live and work—from computer chips, to electric vehicle batteries, to COVID-19 vaccines. While nanoscience is a nascent field - in many ways even younger than the AI field - the applications of nanotechnology are vast and increasingly impactful. In pharmaceuticals, nanomaterials are being used to develop drug delivery systems that target specific cells or tissues with precision, minimizing side effects and enhancing therapeutic efficacy. In chemical manufacturing, nanomaterials serve as catalysts, speeding up reactions and improving energy efficiency. In energy storage, nanomaterials increase the speed of charging, extend the cyclability, and can increase the device capacity and energy density. In automation and robotics, nanomaterials enhance the performance of components such as actuators, sensors, and motors, offering improved strength, flexibility, and responsiveness at the nanoscale. In additive manufacturing, nanomaterials enable the creation of lighter, stronger, and more durable parts, allowing for greater precision and the production of complex, custom-designed structures with enhanced mechanical properties. Nanotechnology is also transforming transportation and construction with stronger, lighter materials, as well as self-healing structures that can extend the lifespan of materials. In the electronics industry, nanomaterials are fundamental to the development of smaller, faster, and more powerful semiconductor chips, enabling the continued miniaturization of devices. Finally, consumer products, such as clothing, cosmetics, and food packaging, also benefit from nanotechnology, with innovations that improve strength and durability, stain resistance, and functionality.